Filtration and water reduction of methyl ester for insulation purpose - A. Rajab; F. E. Putra; J. S. Ramadhani; M. S. I. Silitonga; R. Kurniawan; K. Qibran; Novison Novison; Melda L.; M. I. Hamid; Kiasatina A.; M. F. Akbar; Moh. Kamarol (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
An attempt to develop a monoester type insulating oil, especially methyl ester is being conducted and the current results after conducting two kinds of treatment, namely, filtration and water reduction arereported in this paper. Five different samples were prepared from methyl ester oil based on their melting point. The important properties of oil samples such as breakdown voltage, viscosity, water content, acidity, and density were tested, and are evaluated based on the standard specification of natural ester used for the transformer, ASTM D-6871. Another important property, i.e. oxidation stability was also tested and is evaluated by comparing the corresponding result of mineral oil. It is found that the breakdown voltage, the viscosity and the relative density of the oil fulfill the requirements specified by the standard, whereas other properties like water content, acidity and oxidation stability need further improvement.